2005
DOI: 10.1002/cne.20640
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the density and distribution of sympathetic nerves in spleens from Lewis rats with adjuvant‐induced arthritis suggest that an injury and sprouting response occurs

Abstract: Previously we demonstrated reduced norepinephrine concentrations in spleens from Lewis rats with adjuvant-induced arthritis (AA), an animal model of rheumatoid arthritis. This study extends these findings, examining the anatomical localization and density of sympathetic nerves in the spleen with disease development. Noradrenergic (NA) innervation in spleens of Lewis rats was examined 28 days following adjuvant treatment to induce arthritis or vehicle for the adjuvant by using fluorescence histochemistry for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…Specifically, sympathetic outflow increased in each of the protocols (Shoemaker et al 2001(Shoemaker et al , 2003(Shoemaker et al , 2007. In addition, sympathetic innervation and a-adrenoreceptors have been identified within the walls of the spleen (Lorton et al 2005;Mignini et al 2003). Also, Bakovic et al (2005Bakovic et al ( , 2003 and Stewart et al (2003) observed that a surge in venous catecholamine concentrations was associated with splenic constrictions.…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, sympathetic outflow increased in each of the protocols (Shoemaker et al 2001(Shoemaker et al , 2003(Shoemaker et al , 2007. In addition, sympathetic innervation and a-adrenoreceptors have been identified within the walls of the spleen (Lorton et al 2005;Mignini et al 2003). Also, Bakovic et al (2005Bakovic et al ( , 2003 and Stewart et al (2003) observed that a surge in venous catecholamine concentrations was associated with splenic constrictions.…”
Section: Discussionmentioning
confidence: 91%
“…In spleens of arthritic rats (AIA), the nerve density in white pulp distal to the hilus is reduced considerably, while nerve density in the hilus and red pulp is increased (38). The red pulp, the site where activated immune cells reside and eventually exit the spleen (12), is normally sparsely innervated by sympathetic fibers, but a sympathectomy resulted in a compensatory sprouting of noradrenergic nerves in red pulp of arthritic, but not of nonarthritic rats (38).…”
Section: Sympathetic Innervation Of the Spleen And Joints In Experimementioning
confidence: 99%
“…The red pulp, the site where activated immune cells reside and eventually exit the spleen (12), is normally sparsely innervated by sympathetic fibers, but a sympathectomy resulted in a compensatory sprouting of noradrenergic nerves in red pulp of arthritic, but not of nonarthritic rats (38). The investigators suggested that this altered sympathetic innervation pattern in the red pulp was thought to reflect a regulated microenvironment, where migrated immune cells provide trophic support to the redistributed SNS fibers, which, in turn, could play a critical role in sustaining immune dysregulation seen in chronic inflammatory stages of arthritis (38). In addition, an overall reduction of sympathetic nerve fibers was found in the spleen of DBA/1 mice with early, symptomatic CIA compared with normal DBA/1 mice.…”
Section: Sympathetic Innervation Of the Spleen And Joints In Experimementioning
confidence: 99%
“…However, in these studies, it was unclear how the sympathetic innervation was altered, if at all, in the splenic parenchyma where nerve terminals and immune cells come into direct contact, nor was the mechanism by which the immune system affected sympathetic neurons assessed. Recently, Lorton et al (32) reported a decline of noradrenaline levels and noradrenergic nerve density in the white pulp and the regions distal to the hilus, but increased nerve density in the red pulp and the hilar regions in the spleens of arthritic rats. This finding indicates an injury and compensatory sprouting response with disease development, and the redistribution of sympathetic nerves from the white pulp to the red pulp, and suggests a signal by cytokines and neurotrophins by activated immune cells migrated into the red pulp in arthritic rats.…”
Section: Discussionmentioning
confidence: 99%